Design of a support tool for the selection of AIDC technologies in logistics processes - Ríos Córdova, María Alejandra (2024)
In current supply chains, the use of AIDC technologies allows the information that flows to be standardized and reliable, as well as obtaining a series of advantages related to saving time and costs. In Cuba, the use of these technologies is not regulated by national laws and most companies do not use them, considering ignorance of their effectiveness as the cause. This article analyzes AIDC technologies: specifically, bar code systems and radio frequency systems, their operation and benefits of their use in supply chains. Based on the existing need, a tool was designed based on a procedure that establishes a guide for the selection of technologies to be implemented in logistics processes. The tool designed is used for Case Studies to know its application and mode of use.